Inward Processing Regime Promotion System in Vegetable Oil Industry: A Case Study of Turkey - Sinan Duru; Dilşat Bozdoğan Konuşkan; Oğuz Parlakay (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine applicability of the Inward Processing Regime (IPR) in enterprises which are vegetable oil producers and exporters. The data was obtained from 26 vegetable oil producer and exporter enterprises by using survey method. Frequency tables, indices, and percentage calculating were used to analyse Data. Also, SWOT analysis was used to determine the strengths, weaknesses, opportunities and threats in the sector, and relationship among some variables were examined with correlation coefficient. According to research findings, 25 of the enterprises (96%) utilised the IPR. Since the enterprises started to use that system; availability of cheap raw material, rate of capacity utilisation, market share, and export value all have increased. In addition, raw material was found as an important expense item, and the most important problems were qualified as raw material inadequacy and high input prices.